Worship Motivation in Islam: An Islamic Psychological Analysis of Paradise and Hell - Ramdhani, Dadan; Mahmud, Salami; Jannah, Miftahul (FITRAH: International Islamic Education Journal, 2026)
This study examines worship motivation in Islam by integrating Islamic psychology with contemporary theories of motivation. The focus includes the validity of paradise-hell motivation, the stages of spiritual motivation evolution (maqamat), the dynamics of khauf (praiseworthy fear) and raja' (hope), and the pinnacle of this evolution, namely mahabbah (sincere love), which represents pure intrinsic motivation. The method employed is qualitative, using a library research approach to the Qur'an, authentic Hadith, and classical Sufi works, and analyzing them through content analysis and hermeneutics. The novelty of this research lies in integrating the Sufi concept of maqamat (khauf, raja', mahabbah) with Self-Determination Theory and Maslow's Hierarchy of Needs, revealing conceptual parallels between Islamic and Western psychology that have not been widely developed in prior Islamic psychology studies. This study offers a holistic perspective on the evolution of worship motivation from extrinsic to intrinsic, aiming to achieve inner well-being and Allah's pleasure, and to provide practical implications for the development of Islamic spiritual education.